Maritime trap-jaw ants (Hymenoptera, formicidae, ponerinae) of the indo-australian region – redescription of odontomachus malignus smith and description of a related new species from singapore, including first descriptions of males - Wang, W.Y. (Pensoft Publishers, 2021)
10.3897/zookeys.915.38968